(untitled) (Journal of the Management Sciences, 2025)
Experiential purchase intentions refer to a consumer’s deliberate intention or willingness to buy products, services, or experiences primarily for the emotional, psychological, or sensory experiences they offer rather than their functional or material utility. This study examined the influence of human images in advertisements on consumers’ experiential purchase intention. The study anchored on Hedonic Consumption Theory (Holbrook & Hirschman, 1982) and Self-Determination Theory (Deci & Ryan, 1985), which collectively explain how emotional gratification and intrinsic psychological needs drive consumer engagement with experience-based products when human images are present in advertisements. The study adopted a cross-sectional survey research design. The population of the study comprised of residents of Anambra State, Nigeria. The sample size for the study was 384 respondents using Cochran’s (1977) sample size estimation formula. Data were collected through online survey. The Data were analyzed using descriptive and inferential statistical tools. Findings revealed that human images in advertisements significantly enhance consumers’ emotional connection with products increase memorability, and influence their intention to engage in experiential purchases. The results further showed that demographic variables such as age, gender, and income influence the strength of this effect. The study also found that human images serve as persuasive emotional and motivational cues that intensify experiential purchase intentions. Based on the findings, the study recommends that advertisers and marketers of experiential and luxury goods should strategically integrate expressive and relatable human imagery tailored to target demographics to evoke emotional resonance, stimulate imagination, and boost purchase intentions.